THE MEDIATION EFFECT OF SELF-ESTEEM ON THE RELATIONSHIP BETWEEN PERSONALITY TRAITS AND COLLECTIVE SELF-ESTEEM IN THE SAMPLE OF LATVIAN ARTS THERAPISTS - Krieķe, Zane; Mārtinsone, Kristīne; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this study was to examine the relationship among personality traits, self-esteem and collective self-esteem of Latvian Arts therapists and specifically to examine a potentially mediating role of self-esteem on the correlation between personality traits and collective self-esteem. The sample of the study consisted of 81 Arts therapists of whom data for 74 AT were analysed. The data were collected by Latvian Personality Inventory (LPI-v3), Collective Self-Esteem Scale (CSES), Rosenberg Self-Esteem Scale (RSES) including the demographic data. Pearson correlations indicated significant negative moderate correlation between self-esteem and LPI scale Neuroticism, positive moderate correlation between self-esteem and CSES scale Membership self-esteem and between LPI scale Neuroticism and CSES scale Membership self-esteem, therefore mediation analysis was applied to examine the effect of self-esteem on a relationship between Neuroticism and Membership Self-Esteem. Sobel test was used to test the significance of a mediation effect. Results indicated Self-esteem as a significant mediator in the relationship between Neuroticism and Membership self-esteem. The findings of this research suggest that emotional stability and self-esteem influence Latvian Arts therapist’s sense of identifying themselves as members with their professional group. These results are important for further development of Latvian Arts therapist profession to strengthen Art therapist’s professional identity.